2021
DOI: 10.1111/fog.12558
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variations in diet of Japanese jack mackerel (Trachurus japonicus) juveniles in the southwestern Sea of Japan in relation to recent growth rate

Abstract: We examined interannual variations in the diet of Trachurus japonicus juveniles in relation to prey density and recent 5‐day instantaneous growth rate (IGR) in the southwestern part of the Sea of Japan (SJ) in late spring during 2011–2013. Habitat temperature of juveniles in 2011 was lower than the other 2 years. In all 3 years, more than 97% of juveniles had food in the stomach. Small juveniles <35‐mm standard length (SL) fed mainly on adult female Paracalanus parvus s.l., the most dominant calanoid copepod i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Major prey organisms for larvae and juveniles of T. japonicus have been reported as Paracalanus parvus s. l. (hereafter referred to as P. parvus) and Calanus sinicus in the ECS (Sassa et al, 2019;. Our recent study demonstrated that prey organisms for small (<35 mm standard length, SL) juveniles of T. japonicus used in this study were mainly P. parvus, while those for large (≥35 mm SL) juveniles were C. sinicus during 2011-2013 (Sassa et al, 2021). We therefore assumed that mean density of P. parvus and C. sinicus in waters with occurrence of T. japonicus juveniles would be indicative of the prey abundance for small and large T. japonicus juveniles, respectively.…”
Section: Environmental Conditions Experienced By T Japonicus Juvenilesmentioning
confidence: 64%
“…Major prey organisms for larvae and juveniles of T. japonicus have been reported as Paracalanus parvus s. l. (hereafter referred to as P. parvus) and Calanus sinicus in the ECS (Sassa et al, 2019;. Our recent study demonstrated that prey organisms for small (<35 mm standard length, SL) juveniles of T. japonicus used in this study were mainly P. parvus, while those for large (≥35 mm SL) juveniles were C. sinicus during 2011-2013 (Sassa et al, 2021). We therefore assumed that mean density of P. parvus and C. sinicus in waters with occurrence of T. japonicus juveniles would be indicative of the prey abundance for small and large T. japonicus juveniles, respectively.…”
Section: Environmental Conditions Experienced By T Japonicus Juvenilesmentioning
confidence: 64%